2014
DOI: 10.1021/jz5009483
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Mobile Pt Species by PdO Nanoparticles under Oxidizing Conditions

Abstract: Pt is an active catalyst for diesel exhaust catalysis but is known to sinter and form large particles under oxidizing conditions. Pd is added to improve the performance of the Pt catalysts. To investigate the role of Pd, we introduced metallic Pt nanoparticles via physical vapor deposition to a sample containing PdO nanoparticles. When the catalyst was aged in air, the Pt particles disappeared, and the Pt was captured by the PdO, forming bimetallic Pt-Pd nanoparticles. The formation of metallic Pt-Pd alloys un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 12 publications
3
62
1
Order By: Relevance
“…As expected, [39] the addition of palladium to platinum preventedi ts excessive sintering, which also can be seen in the TEM images of the calcined catalysts ( Figure 1). Ar icher palladium content of the catalysts resultsi nal ower degree of sintering.…”
Section: Resultssupporting
confidence: 81%
“…As expected, [39] the addition of palladium to platinum preventedi ts excessive sintering, which also can be seen in the TEM images of the calcined catalysts ( Figure 1). Ar icher palladium content of the catalysts resultsi nal ower degree of sintering.…”
Section: Resultssupporting
confidence: 81%
“…[3]When Pt nanoparticles were deposited on a planar model SiO 2 supportas a separate phase, heating for only 2 minutes at 650 °C in air caused the formation of bimetallic PtPd particles. [7] This previous work demonstrates that Pt species are mobile andcan be effectively trapped by PdO at high temperatures in air, forming bimetallic PtPd particleswhich are thermodynamically more stable. [7] The migration and vapor phase transport of precious metals in automotive exhaust catalysts has been documented in the literature.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that Pt is very mobile at high temperatures in oxidising environments and can be effectively trapped by PdO nanoparticles ,. The studies demonstrated that upon heat treatment of specimens with initially separated Pt and PdO nanoparticles, the highly mobile Pt is trapped by the more stable PdO nanoparticles and alloyed Pt–Pd nanoparticles are formed, which are thermodynamically more stable and slow down further sintering by Ostwald ripening as well as the emission of Pt into the vapour phase .…”
Section: Resultsmentioning
confidence: 97%